2008
DOI: 10.1111/j.1529-8019.2008.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

A medical alternative to the treatment of compensatory sweating

Abstract: Compensatory sweating after sympathectomy does not have a satisfactory, free-of-secondary-effects treatment. Glycopyrrolate has been successfully used to treat other types of hyperhidrosis. Compensatory sweating after sympathectomy could respond to the topical application of glycopyrrolate. Ten patients were selected with compensatory sweating after sympathectomy. One milliliter of a 2% water solution of topical glycopyrrolate was applied once a day over the affected area and massaged for 30 seconds. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…11 Eight of 10 patients with compensatory HH after sympathectomy responded to treatment with 2% glycopyrrolate solution. 12 In a singleblinded right-left comparison study in 20 patients with palmoplantar HH, glycopyrrolate iontophoresis was significantly more effective than tap water iontophoresis. 13 Clonidine is indicated for treatment of hypertension, functioning as a centrally acting alphaadrenergic receptor agonist that reduces sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…11 Eight of 10 patients with compensatory HH after sympathectomy responded to treatment with 2% glycopyrrolate solution. 12 In a singleblinded right-left comparison study in 20 patients with palmoplantar HH, glycopyrrolate iontophoresis was significantly more effective than tap water iontophoresis. 13 Clonidine is indicated for treatment of hypertension, functioning as a centrally acting alphaadrenergic receptor agonist that reduces sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of glycopyrrolate in the hyperhidrosis treatment is via prevention of acetylcholine-induced stimulation of sweat gland receptors. In a prospective clinical trial which was performed by Cladellas et al [14] topical glycopyrrolate administration to the compensatory hyperhidrosis area was found effective in controlling symptoms. Long-term efficiency and safety results of treatment is not known and anticholinergic side effects of glycopyrrolate such as dry mouth, visual disturbance, urinary retention, urgency, flushing, and constipation should be kept in mind.…”
Section: Resultsmentioning
confidence: 98%
“…It is more potent than atropine, another cholinergic agent, and has less undesirable effects because of an inability to cross the blood-brain barrier. To avoid systemic absorption and side effects such as dry mouth, visual disturbance, and urine retention, topical glycopyrrolate has been assessed in many studies, which have shown it to be an effective, safe, and satisfactory treatment for craniofacial hyperhidrosis, 134,135 compensatory sweating after sympathectomy, 136 and gustatory hyperhidrosis. 137,138 This treatment modality is well tolerated in most patients apart from transient dry mouth, sore throat, accommodative failure, and headache in a few patients.…”
Section: Drugs Acting At Synaptic and Neuroeffector Junctional Sites mentioning
confidence: 99%
“…137,138 This treatment modality is well tolerated in most patients apart from transient dry mouth, sore throat, accommodative failure, and headache in a few patients. [135][136][137] Topical botulinum toxin type A Botulinum toxin type A (BTX-A), a 900-kd neurotoxin, prevents release of neurotransmitter acetylcholine from the presynaptic membrane at neuromuscular junctions and in cholinergic autonomic neurons.…”
Section: Drugs Acting At Synaptic and Neuroeffector Junctional Sites mentioning
confidence: 99%